Crystallization of polymers - Mandelkern, Leo (Crystallization of polymers, 2002)
The Crystallization of Polymers 2nd Edition provides a self-contained, comprehensive, and up-to-date treatment of polymer crystallization. Volume I is a presentation of the equilibrium concepts that serve as a basis for the subsequent volumes. It will be an invaluable reference work for all scientists who work in the area.